1971
DOI: 10.1111/j.1365-2672.1971.tb01007.x
|View full text |Cite
|
Sign up to set email alerts
|

An Initial Approach to the Taxonomy of Some Gram Negative Yellow Pigmented Rods

Abstract: SUMMARY: The responses of various groups of Gram negative, yellow pigmented rods constructed on the basis of classical criteria to a wide range of cultural and biochemical features were examined. The occurrence of a wide area of slime surrounding true growth with isolates which may spread but did not glide is described. The correlation between the classical groups and divisions suggested on the basis of pigment absorption curves was examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
28
0

Year Published

1977
1977
2010
2010

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…F . pectinovorum NCIB 9059 is an orange-yellow-pigmented, gram-negative, aflagellate rod which exhibits gliding motility (17, 18, 231, although spreading on agar media has not been evident in previous work (18,21,23). It has been suggested that this species be reassigned to Brisou's yellow, nonmotile genus Empedobacter (5; P. Kaiser, Ph.D. Thesis, University of Paris, Paris, France, 1971), but the consensus is that this organism more properly belongs in the genus Cytophaga (17, 18, 21, 32).…”
mentioning
confidence: 99%
“…F . pectinovorum NCIB 9059 is an orange-yellow-pigmented, gram-negative, aflagellate rod which exhibits gliding motility (17, 18, 231, although spreading on agar media has not been evident in previous work (18,21,23). It has been suggested that this species be reassigned to Brisou's yellow, nonmotile genus Empedobacter (5; P. Kaiser, Ph.D. Thesis, University of Paris, Paris, France, 1971), but the consensus is that this organism more properly belongs in the genus Cytophaga (17, 18, 21, 32).…”
mentioning
confidence: 99%
“…Medium B contained (w/v) 0.2 % Bacto peptone (Difco), 0.2 % casein hydrolysate (Merck), 0.2 % Bacto yeast extract (Oxoid), 0.1 % glucose, 0.02 % KH 2 PO 4 , 0.005 % MgSO 4 . 7H 2 O and 1.5 % Bacto agar (Oxoid) in 50 % (v/v) natural seawater and 50 % (v/v) distilled water at pH 7.5-7.8, as described elsewhere (Ivanova et al, 1996).The phenotypic properties used for the characterization of Flavobacterium species were determined by using standard procedures (Smibert & Krieg, 1994) and as described elsewhere (McMeekin et al, 1971;Ivanova et al, 1996Ivanova et al, , 1998Ivanova et al, , 2005Bernardet et al, 2002). Strain 022-2-26 T was cultured at 22-24 u C. To test for spreading growth and gliding motility, strain 022-2-26 T was grown on medium B with the peptone content reduced to 0.02 % (0.2 g l 21 ).…”
mentioning
confidence: 99%
“…The phenotypic properties used for the characterization of Flavobacterium species were determined by using standard procedures (Smibert & Krieg, 1994) and as described elsewhere (McMeekin et al, 1971;Ivanova et al, 1996Ivanova et al, , 1998Ivanova et al, , 2005Bernardet et al, 2002). Strain 022-2-26 T was cultured at 22-24 u C. To test for spreading growth and gliding motility, strain 022-2-26 T was grown on medium B with the peptone content reduced to 0.02 % (0.2 g l 21 ).…”
mentioning
confidence: 99%
“…The strains examined (see Table 2 ) were named Flavobacterium species from the American Type Culture Collection and the National Collection of Industrial Bacteria, and unnamed strains of known % GC from the collection of Dr J. M. Shewan, Aberdeen, or isolated by McMeekin et a/. (1971McMeekin et a/.…”
Section: E T H O D Smentioning
confidence: 99%